GENETIC POLYMORPHISM OF β-LACTOGLOBULIN GENE IN INDIGENOUS NIGERIAN GOAT BREEDS - Ezewud, Anthony E; Abubakar, Rukayyat Geka; Egena, Acheneje S.S.; Alabi, John O. (Journal of Agricultural Sciences (Belgrade), 2019)
Polymorphism at the β-Lactoglobulin (β-LG) gene of three Nigerian goat breeds namely: the West African Dwarf, Sahel and Red Sokoto goats was investigated using the Polymerase Chain Reaction-Random Fragment Length Polymorphism (PCR-RFLP) method. The restriction endonucleases used in the study were Rsal and Mspl, respectively. The results revealed the existence of only one polymorphic variant (allele A) with a gene frequency of 1.0 in all the three goat breeds studied. The amplified products were observed at 120 bp and the restriction digestion with Rsal revealed just one genotype at the β-LG locus. It was concluded that there is the absence of polymorphism at the β-LG locus of the goats investigated.